Remote Sensing Retrieval of Isoprene Concentrations in the Southern Ocean - Rodriguez-Ros, Pablo; Gali, Marti; Cortes, Pau; Robinson, Charlotte; Antoine, David; Wohl, Charel; Yang, MingXi; Simo, Rafel (Wiley-Blackwell, 2020)
Isoprene produced by marine phytoplankton acts as a precursor of secondary organic aerosol and thereby affects cloud formation and brightness over the remote oceans. Yet the marine isoprene emission is poorly constrained, with discrepancies among estimates that reach 2 orders of magnitude. Here we present ISOREMS, the first satellite‐only based algorithm for the retrieval of isoprene concentration in the Southern Ocean. Sea surface concentrations from six cruises were matched with remotely sensed variables from MODIS Aqua, and isoprene was best predicted by multiple linear regression with chlorophyll a and sea surface temperature. Climatological (2002–2018) isoprene distributions computed with ISOREMS revealed high concentrations in coastal and near‐island waters, and within the 40–50°S latitudinal band. Isoprene seasonality paralleled phytoplankton productivity, with annual maxima in summer. The annual Southern Ocean emission of isoprene was estimated at 63 Gg C yr−1. The algorithm can provide spatially and temporally realistic inputs to atmospheric and climate models.